TOWARDS AUTONOMIC SEMANTIC-BASED MANAGEMENT OF DISTRIBUTED APPLICATIONS - Funika, Włodzimierz; Kupisz, Mateusz; Koperek, Paweł (Computer Science, 2013)
In this paper we present our approach to the management of distributed systems basedon semantic description of available resources. We use ontologies for a semantic descriptionof the monitored system and other aspects of monitoring and management (such as metrics)and introduce a feedback loop on underlying infrastructure. Such an approach allows toautomate monitoring and the ease the work of administrator. We introduce concepts behinda novel automatic management system, SAMM, developed within our research. We discussthe core mechanisms used in the system – the estimation of future measurements, approachto knowledge gathering, and the process of decision making. Then we provide some detailson the architecture and implementation of SAMM.